2022
DOI: 10.3389/fphar.2022.845324
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Increase of Collagen/Fibrin Deposition and High PAI-1 Production in Human Nasal Polyps

Abstract: Objective: Our previous studies showed an age-related increased prevalence of nasal polyps (NP) and reduced production of S100A8/9 in elderly patients with chronic rhinosinusitis with NP (CRSwNP). In this study, we investigated an unbiased age-related gene expression profile in CRSwNP subjects and healthy controls, and further identified the differences in their tissue remodeling.Methods: Microarrays using NP and uncinate tissues from health controls (elderly, age ≥65 vs. non-elderly, age 18–49) were performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 47 publications
(55 reference statements)
2
6
0
Order By: Relevance
“…44 However, data supporting the association of T2 inflammation to SERPINB2 in CRSwNP are more limited, with a previous microarray study reporting increased SERPINB2 RNA expression in nasal polyp tissues as compared with HCs. 19 In the current study, we showed that SERPINB2 mRNA and protein were significantly increased in NPs from CRSwNP subjects as compared with HCs. A recent lower airway single-cell RNA sequencing study of asthma showed that SERPINB2 is one of the core genes which upregulated in all subtypes of bronchial epithelial cells.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…44 However, data supporting the association of T2 inflammation to SERPINB2 in CRSwNP are more limited, with a previous microarray study reporting increased SERPINB2 RNA expression in nasal polyp tissues as compared with HCs. 19 In the current study, we showed that SERPINB2 mRNA and protein were significantly increased in NPs from CRSwNP subjects as compared with HCs. A recent lower airway single-cell RNA sequencing study of asthma showed that SERPINB2 is one of the core genes which upregulated in all subtypes of bronchial epithelial cells.…”
Section: Discussionsupporting
confidence: 49%
“…SERPINB2, which is upregulated in asthma and associated with type-2 inflammation and asthma severity, is crucial for collagen fibrin deposition under epithelial layer in the airways. 19 In this study, we expand the disease implications of SERPINB2…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Age as well as gender may additionally impact collagen deposition in different tissues. Increased collagen and fibrin deposition occurred in elderly normal controls when compared to non-elderly controls, and this was even more pronounced in elderly patients with nasal polyps (146), which was further confirmed by studying model organisms such as mice and C. elegans (147). The deposition of collagen fibers after surgery is significantly reduced in older men but not in women (148).…”
Section: Age and Sex In Collagen Depositionmentioning
confidence: 82%
“…Subsequent subset analysis revealed enhanced glycolytic and hypoxia metabolism in subsets 1 and 6, predominantly present in nasal polyp tissues and exhibiting high expression of genes associated with collagen synthesis, particularly the collagenrelated gene P4HA1 (Figure 1D). Notably, studies have indicated a significant increase in collagen fibres in nasal polyps, 6 which may offer novel insights into the pathogenesis and treatment of CRSwNP.…”
Section: Bulk and Single-cell Transcriptome Sequencing Reveal The Met...mentioning
confidence: 99%